Caught between King, Religion, and Social Ambition: Marc-Antoine Marreau De Boisguérin and His Family (ca. 1560-1680) - Bezzina, Edwin (The sixteenth century journal, 2008)
This case study investigates the choices made by a newly ennobled French Protestant and his family. During the French Wars of Religion, Marc-Antoine Marreau de Boisguérin advanced his social ambitions and acquired noble title through military service to the crown. As the crown became more Catholic, Boisguérin experienced greater difficulty remaining Protestant. After a period of defying the royal will, Boisguérin acquiesced and crossed confessional lines, but he never became a Catholic militant. He also shaped the professional and confessional configuration of his family. His progeny were able to retain a degree of flexibility, producing a confessionally heterogeneous family compact.